Fission yield covariance matrices for the main neutron-induced fissioning systems contained in the JEFF-3.1.1 library. (November 2017) - Terranova, N.; Serot, O.; Archier, P.; De Saint Jean, C.; Sumini, M.
Highlights: A covariance generation methodology has been developed for the JEFF-3.1.1 fission yield library. Fission yield covariance matrices have been produced for the most important fissioning systems. The JEFF-3.1.1 fission yield library and several experimental data on miscellaneous fission quantities have been represented. Fission yield covariance matrices have been propagated in elementary fission decay heat calculations. Abstract: Nuclear data improvement, validation and completion are one of the major concerns for ensuring safety-by-design standards and economic optimization for modern nuclear facilities. Uncertainty and sensitivity analyses must be carried out to estimate the nuclear data influence on integral reactor parameters, highlighting margins of improvement needed to get full benefit from modern advanced modeling. The quality of any uncertainty quantification analysis strongly depends on the covariance matrices made available in the evaluated nuclear data libraries. In modern nuclear data libraries (e.g. JEFF, ENDF/B or JENDL) no correlations for fission yields (FY) are provided, so in the present work we propose a covariance generation methodology which yielded reasonable results for application-relevant thermal and fast neutron-induced fission product yields. The main goal was not to perform a new evaluation but to reproduce coherently the JEFF-3.1.1 fission yield library and add covariance information. We did so using the Generalized Least Square Method (GLSM) and the Marginalization techniques implemented in the CONRAD code, developed at CEA-Cadarache. Results on the thermal neutron-induced fission of 235 U, 239 Pu, 241 Pu and on the fast-neutron induced fission of 238 U, 239 Pu and 240 Pu are presented and tested on elementary fission decay heat uncertainty quantifications.